PENYULUHAN DAN PELATIHAN PEMBUATAN PESTISIDA NABATI CAIR DI DESA TALANGKEMBAR, MONTONG, TUBAN - Burhanatut Dyana; Muhammad Romadhon Habibullah; Irvia Nazilatul Qodriyah; A’immatur Rosidah; Umi Rahayuningtyas (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Talangkembar village, Montong, Tuban, East Java is an agricultural village in the highlands, so that the majority of the people work in the agricultural sector. Corn is the main crop of Talangkembar village farmers. A good harvest with a high selling price is the hope of the farmers, however this is difficult to realize because the plants are often attacked by “putehen” pests and exacerbated by limited subsidized fertilizers. Seeing this problem, researchers provide a solution through training in the manufacture of liquid organic fertilizers or liquid vegetable perticides as an alternative in protecting plants from “putehen” pests as well as the limitations and dependence of farmers on subsidized fertilizers. This service is carried out for one month using the agricultural training extension method and partnering with a combination of farmer groups (Gapoktan) and the Agricultural Extension Center (BPP) in Montong district. Through this service, it is hoped that farmers will be able to make liquid organic fertilizer independently with ingredients that are easy to find and economical, so that they are able to overcome “putehen” pest attacks and farmer’s dependence on subsidized fertilizers which have an impact on optimizing planting and maximum yields.